2023
DOI: 10.3389/fpsyt.2023.1098734
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neuropsychiatric disorders in patients with systemic lupus erythematosus in Pakistan: A systematic review and meta-analysis

Abstract: IntroductionBy conducting a systematic review and meta-analysis, we investigated the prevalence of neuropsychiatric (NP) symptoms among systemic lupus erythematosus (SLE) patients in Pakistan.MethodsIn this review work, three electronic databases (Web of Science, MEDLINE, and Google Scholar) and local databases were screened for 20 years from 1 January 2002 to 30 September 2022, to identify the articles evaluating the prevalence of NP symptoms in SLE patients in Pakistan. We performed a random-effects meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
(89 reference statements)
0
6
0
1
Order By: Relevance
“…We set the con dence interval (CI) at 99% with a margin of error (E) of 1.5%. A previously conducted systematic review (17) reported a pooled prevalence of malaria in Pakistan of 23.3%, which we set as our estimated population proportion (p). Based on the population size, these values were put into the software, which gave us a sample size of 2540 using the following equation:…”
Section: Sample Sizementioning
confidence: 99%
“…We set the con dence interval (CI) at 99% with a margin of error (E) of 1.5%. A previously conducted systematic review (17) reported a pooled prevalence of malaria in Pakistan of 23.3%, which we set as our estimated population proportion (p). Based on the population size, these values were put into the software, which gave us a sample size of 2540 using the following equation:…”
Section: Sample Sizementioning
confidence: 99%
“…Autoantibodies, activation of the complement system and microglia mediate neurotoxicity, which results from disruption of the integrity of the blood-brain barrier [87]. Autoantibodies and cytokines can have local or widespread effects on the central nervous system [88,89]. Alternative theory says that Interferon-alpha (IFN-α) is the main factor in the pathogenesis of SLE.…”
Section: Cognitive Disordersmentioning
confidence: 99%
“…Autoprzeciwciała, aktywacja układu dopełniacza i mikrogleju pośredniczą w neurotoksyczności, która wynika z zaburzenia integralność bariery krew -mózg [87]. Autoprzeciwciała i cytokiny mogą mieć miejscowy lub rozległy wpływ na ośrodkowy układ nerwowy [88,89]. Odmienna teoria mówi o tym, że Interferon-alfa (IFN-α) to główny czynnik w patogenezie SLE.…”
Section: Zaburzenia Poznawczeunclassified
“…The autoimmune disorder systemic lupus erythematosus (SLE) is one of the most common types of lupus in which the immune system attacks its own tissues [ 1 ]. SLE can cause inflammation and damage to almost every organ system in the body including the brain, skin, joints, and lungs.…”
Section: Introductionmentioning
confidence: 99%